Impact of peritoneal transport characteristics on cardiac function in paediatric peritoneal dialysis patients: a Turkish Pediatric Peritoneal Dialysis Study Group (TUPEPD) report - AKALIN, FİGEN; YILDIZ, NURDAN (OXFORD UNIV PRESS, 2010)
Methods. One hundred and ten PD patients (13 +/- 5 years, PD vintage: 31 +/- 27 months) were enrolled into the study. Four-hour dialysate/plasma creatinine ratio was used for differentiating PET groups. Thirty-eight patients were high transporters, 29 were high-average transporters and 43 were low-average/low transporters. Echocardiography was performed in all subjects. Results. Age, PD vintage, dialysate glucose concentration, ultrafiltration volume, urine volume and blood pressure levels were similar in all PET groups. No biochemical or echocardiographic data (ejection fraction, fractional shortening, left ventricular mass index, myocardial performance index, power Doppler E/tissue Doppler E ratio reflecting diastolic function) were different among PET groups except lower albumin (P = 0.025) levels in high transporters and higher high-sensitivity C-reactive protein (P = 0.026) levels in high and high-average transporters compared to other transport groups. Conclusions. Cardiac structural and functional abnormalities are highly prevalent among paediatric PD patients. Transport rates did not have a significant effect on biochemical parameters or cardiac structural/functional parameters. It might be suggested that being a high transporter does not provide a disadvantage in terms of atherogenic tendency and cardiac disease in paediatric PD patients. Oligoanuria, anaemia and hypertension were independent predictors of cardiac disease.
Keywords: cardiac function; children; echocardiography; peritoneal dialysis; peritoneal equilibration test; RESIDUAL RENAL-FUNCTION; LEFT-VENTRICULAR MASS; MEMBRANE-TRANSPORT; CAPD PATIENTS; EQUILIBRATION TEST; NUTRITIONAL-STATUS; TECHNIQUE FAILURE; SOLUTE TRANSPORT; SHORT PET; CHILDREN